G21(P) An audit of handover from the Children's Emergency Department (CED) to the ward. (7th April 2014) - MacLeod, R; Christian, W
Abstract : Background: Patient handover taking place between the Children's Emergency Department (CED) and the ward to which the patient is being transferred is essential for patient safety. Poor or incomplete information can delay care, lead to confusion or, occasionally, lead to disastrous consequences. It is the duty of every doctor to ensure good handover takes place. It is important to optimise communication of critical information as an essential component of risk management and patient safety. Therefore we aim to assess the prevalence of patient handover taking place and the content of this being recorded in the notes. Method: Fifty-four sets of notes of patients admitted to the wards from CED in October 2012 were randomly selected and audited against the following standards with 100% target for all: Written record of handover in the notes either by use of handover stamp, freehand notes entry or using handover sheet; clearly documented name of doctors giving and accepting handover; handover should be timed, dated and signed; good guality of handover using SBAR or similar format to convey information concisely (a minimum of a background, recent clinical observations and clear recommendations). A new handover document was then introduced in combination with a programme to educate and raise awareness among staff and then handover was re-audited with fifty-one sets of notes. Results: Conclusion: The introduction of a new handover document increased the frequency of documentation and quality of handover, thus improving patient safety. Further work is required to increase the frequency of recording the doctors involved in handover and timing, dating and signing the document. Work on further updating the handover document is underway and this will be re-audited after it is introduced.